REVENUE FROM REGENCY/CITY REGIONAL TAX AND RETRIBUTION SHARING TO SUPPORT THE PERFORMANCE OF THE KRAGAN VILLAGE GOVERNMENT IN EAST JAVA PROVINCE - Suyanto Suyanto; Sri Warjiyati (Universitas Nusa Cendana, 2022)
Purpose of this study is to analyze the effects of local taxes and retribution in influencing the performance of the Kragan village government in East Java Province. Methodology is a quantitative approach. The analyzed data sources is the Human Development Index (HDI) obtained from the Central Bureau of Statistics. While the data used are cross sectional and time series taken from 2015 - 2020. Study findings revealed that regional tax revenues increase in regional taxes, the more various activities that can be funded with local taxes. Thus it will also have a positive impact on the performance of the village government in implementing regional autonomy which aims to improve the welfare of the community. Limitations in this study is related to tax management in the region. Suggestions for the Kragan village government in East Java Province are to supervise the implementation and collection of regional taxes and retribution. So that both can be used in improving the welfare of the community. Future researchers may ensure the completeness of data sources and uniformity of methods from the data used. Keywords: Regions, Retribution, Taxes, Welfare